2015
DOI: 10.3390/su7089943
|View full text |Cite
|
Sign up to set email alerts
|

Toward Sustainable Economic Growth: A Spatial Panel Data Analysis of Regional Income Convergence in US BEA Economic Areas

Abstract: Abstract:A question fundamental to sustainable economic growth is whether a poor region tends to grow faster than a rich one, such that the poor region catches up with the rich region in terms of the level of per capita income. In this article, we apply the spatial panel data approach to the analysis of regional income convergence across 177 economic areas in the contiguous US states over the period from 1969 to 2009. Using data on per capita incomes in the functionally defined economic areas, we find that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
1
2
0
Order By: Relevance
“…That is, the convergence rate is lower in spatial autoregressive models. Such results are quite expected and are supported by a number of studies devoted to modeling convergence using spatial panel data models (Abreu et al, 2005;Arbia et al, 2008;Lim & Kim, 2015) and can be interpreted as follows. The β parameter in the spatial autoregressive model represents only the direct marginal effect of increasing the initial consumption level, while the β parameter in the spatial error model accumulates the influence of both the direct marginal effect and indirect effects.…”
Section: Introduction and Review Of Literaturesupporting
confidence: 70%
See 2 more Smart Citations
“…That is, the convergence rate is lower in spatial autoregressive models. Such results are quite expected and are supported by a number of studies devoted to modeling convergence using spatial panel data models (Abreu et al, 2005;Arbia et al, 2008;Lim & Kim, 2015) and can be interpreted as follows. The β parameter in the spatial autoregressive model represents only the direct marginal effect of increasing the initial consumption level, while the β parameter in the spatial error model accumulates the influence of both the direct marginal effect and indirect effects.…”
Section: Introduction and Review Of Literaturesupporting
confidence: 70%
“…For example, Giuseppe Armani and Gianfranco Piras (Aria & Piras, 2004) showed that taking into account spatial interaction in the convergence analysis significantly improves the estimated values of the convergence rate between European regions. A thorough analysis of convergence between European regions using spatial econometric models was carried out in the studies (Armstrong, 1995;López-Bazo et al, 2004;Fingleton & Lopez-Bazo, 2006;Piras & Arbia, 2007;Rey & Le Gallo, 2009), between regions of the USAin the studies (Rey & Montouri, 1999;Lim & Kim, 2015). Also, the concept of convergence using spatial econometric models has been discussed not only in the literature on economic growth.…”
Section: Introduction and Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation